Promoting grain production through high-standard farmland construction: Evidence in China - Shuai Hao; Guogang Wang; Yantao Yang; Sicheng Zhao; Shengnan Huang; Liping Liu; Huanhuan Zhang (Journal of Integrative Agriculture, 2024)
Food security is a strategic priority for a country’s economic development. In China, high-standard farmland construction (HSFC) is an important initiative to stabilize grain production and increase grain production capacity. Based on panel data from 31 sample provinces, autonomous regions, and municipalities in China from 2005–2017, this study explored the impact of HSFC on grain yield using the difference-in-differences (DID) method. The results showed that HSFC significantly increased total grain production, which is robust to various checks. HSFC increased grain yield through three potential mechanisms. First, it could increase the grain replanting index. Second, it could effectively reduce yield loss due to droughts and floods. Last, HSFC could strengthen the cultivated land by renovating the low- and medium-yielding fields. Heterogeneity analysis found that the HSFC farmland showed a significant increase in grain yield only in the main grain-producing areas and balanced areas. In addition, HSFC significantly increased the yields of rice, wheat, and maize while leading to a reduction in soybean yields. The findings suggest the government should continue to promote HSFC, improve construction standards, and strictly control the “non-agriculturalization” and “non-coordination” of farmland to increase grain production further. At the same time, market mechanisms should be used to incentivize soybean farming, improve returns and stabilize soybean yields.